(untitled) (Mariya’s Demo Journal of Advanced Birdwatching, 2025)
Bird migration remains one of the most fascinating yet complex natural phenomena. Recent advancements in GPS tracking and artificial intelligence (AI) have revolutionized the way scientists monitor migratory routes, stopover sites, and habitat preferences. This study explores the integration of AI-powered data analysis with GPS telemetry to improve the accuracy of migratory bird tracking. We analyze movement patterns of several species across continents and discuss how these technological innovations contribute to conservation efforts, particularly in identifying critical habitats and mitigating threats from climate change and habitat destruction.